A importância do Parque Ecológico do Rio Cocó como potencial atrativo turístico - Lopes, Francisco Tiago Moreira Távora (2010)
Due to the great concern about the climate which in the last years has become remarkable, parks gain importance as they represent a conquest of necessary areas for a good urban life quality and for integrating different dimensions becoming areas for leisure, culture, sports, health, education, collective life and tourism promotion. Following this approach, this work presents the ecologic park as an additional option for the people in Ceará as well as for the tourists, as an alternative to the crowded shopping centers, to Beira Mar Avenue seashore full of peddlers and to the already traditional “sun and beach” tourism. Furthermore, it retrieves the local ecological balance. Therefore, it is presented as a main aim, to consider the importance of Cocó River Ecologic Park as a Touristic attraction of Fortaleza City – Ceará for the demands of local and global tourism. The aim is to attract more people to the mentioned region, the tourists as well as the people from Fortaleza, through evoking the awareness of local people and Fortaleza’s tourism workers. The methodology used to the accomplishment of this research was basically through bibliographic research, internet sites, and documented technical visits using pictures referring to the three big areas which forms the totality of Cocó River Ecologic Park: Adahil Barreto Park, Cocó Rail Park and Tancredo Neves Park, and it also used the application of an specific quiz only to the site located at the crossing of Santana Júnior Avenue and Padre Antonio Tomáz Avenue, as it is an area that is more known because of its significant approach which are the tracks, and also because, with all the problems that have been detected, it is exactly in this urbanized area that the more remarkable site is located, compiling with the three bridges which form the park totality. The work searches through this to verify the visitor profile and evaluate the tourists and inhabitant’s satisfaction, that is, the area visitors, compiling pieces of information so that it can be known the point o view of the ones who use the area, if it is or if it is not adequate to the community expectations. Concluding that the Cocó Ecologic Park, regarding the results that are presented, show spatial alterations and its consequences due to extreme vulnerability to physical changes that the park has experienced mainly because of the lack of the lack of fulfillment of its foundation decree. It is seen in its totality in an ongoing process of degradation which in certain moments is valorized only in determined areas and isolated in others, without any support for minimal infrastructure as an essential condition to supply the touristic demand. For this reason, some solutions are proposed with the intention that the research promotes the development.